A Low-Profile Electrically Small Serrated Rectangular Patch Antenna for RFID Applications - Majji, Naveen Kumar; Madhavareddy, Venkata Narayana; Immadi, Govardhani; Ambati, Navya (Engineering, Technology & Applied Science Research, 2024)
This paper presents the design and analysis of a global system for mobile communication applications, as well as the design and analysis of a compact, bidirectional Electrically Small Antenna (ESA) at 0.9 GHz for Radio Frequency Identification (RFID) applications. In order to attain results at lower frequencies while keeping a compact size, the proposed design consists of a microstrip patch antenna in which an SRR and a semicircular-shaped SRR were subtracted from the ground plane. The dimensions of the FR4 substrate, on which this ESA was designed, were 20 × 18 × 1.6 mm. Ansys HFSS was used for the design and simulation of the antenna. Chemical etching was implemented to fabricate the ESA and MS2037C Anritsu Combinational Analyzer was applied for testing. The simulated results show that at 0.9 GHz, the ESA achieves a bandwidth of 300 MHz (700 MHz-1000 MHz). At the resonance frequency, a bidirectional radiation pattern with a 80% radiation efficiency is obtained in both H and E planes. A 90% agreement between the simulated and the fabricated results has been achieved.